Written emotional expression in schools: Processing psychological and emotional stress through narrative writing. - Sassu, Kari A.; Bray, Melissa A.; Gelbar, Nicholas; Kerzner, Tiffany P. (Promoting mind–body health in schools: Interventions for mental health professionals., 2020)
Keywords: dept.csp

Students’ perceptions of career counselling: an examination of a graduate curriculum in the United States - Lindo, Natalya A; Ceballos, Peggy L; Blalock, Sarah; Conner, Charmaine; Edwards, Josh; Spellings, Maria; Webster, Lindsay; Opiola, Kristie (British Journal of Guidance & Counselling, 2020)
Despite its importance as a core counselling competency, less attention is given to career counselling than to other counselling specialties and it is often dismissed as a non-essential category in the counselling field. Because students’ perceptions of career counselling are affected by peer and faculty attitudes it is important to examine the training needs and experiences of graduate counselling students. Therefore, in the current study we utilised a phenomenological approach to examine students’ perceptions of a career counselling curriculum, and its impact on overall views of career counselling. Analysis of in-depth interviews yielded five major themes: View of Career Counselling, Course Delivery, Theory, Application of Knowledge, and Connection between Career Counselling and Personal Counselling. © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Career counselling; career theory; counselling theory; counsellor education; dept.csp; peer-reviewed; personal counselling